Imaging features of breast lymphangioma: A rare case report - Neha Singh, MD; Guriya Kumari, MD; Deepak Kumar Singh, MCh (Radiology Case Reports)
Lymphangioma of the breast is an exceptionally rare benign tumor, often posing significant diagnostic challenges due to its rarity and nonspecific imaging characteristics. We present the case of a 56-year-old female who presented with a painless, gradually enlarging mass in her right breast. Diagnostic imaging, including mammography, ultrasound (USG), and contrast-enhanced magnetic resonance imaging (CEMRI), played a crucial role in identifying the condition. This case underscores the importance of including lymphangioma in the differential diagnosis of cystic breast masses.